Superficial thrombophlebitis of the breast (Mondor disease). - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
Mondor disease is a thrombophlebitis of the thoracic-epigastric superficial vein. It is more frequent in females than in males. In 50% of cases Mondor disease is associated with pain and in 25% with a tension sensation. Mondor disease is more frequently due to traumas, spontaneous or surgical, infections and mammary disorders of various type, from pregnancy to carcinoma. Clotting disorders and hepatitis C act as favoring factors.